Pedagogia universitária: o programa CICLUS e as significações imaginárias na formação continuada de professores universitários - Vasconcellos, Vanessa Alves da Silveira de (2011)
This research was developed and presented to the Postgraduation Program in Education, Master‟s Course of the Education Center of Universidade Federal de Santa Maria, in the Line Formation, Knowledge and Professional Development, considering the perspective of university teaching and of the formation of professionals that participate of such education process. The main aim of such investigation was to understand and analyze the professional trajectory and the formation processes of teachers who participated of the Institutional Program of Professional Development and Formation of Teachers and Managers CICLUS of Universidade Federal de Santa Maria. Facing a reality in which university teaching is not ruled under a specific course, but developed through postgraduation courses, I focused, since my undergraduate studies, on the perspective of issues regarding the process of formation of the formation teacher and his/her formation processes. My starting point, as regards the construction of the thesis, was such concern, as well as my trajectory in researches, readings, events and writings about such theme. Thus, the research was planned believing in the possibility of thinking about a kind of university pedagogy which contemplates the epistemological complexity required by such level of education, considering university teachers who are self-conscious about their role, as well as agents of other teacher‟s formation. Such investigation intended to create new senses to university teaching reality, and was constituted from imaginary meanings built by teachers who participated in CICLUS, throughout their trajectories. The biographical methodological approach was used, through semi-structured interviews, aiming to evidence the educational experiences of the subjects, understanding different processes and mechanisms underlying their formation. Such reports convey that the participants detect contradiction regarding the demanded formation to work with university teaching, and constituted their manner of teaching based on the references of teachers that were important for them at school, and in higher education level. I observe the need to search for other meanings regarding knowledge built through experience, in the light of theories, reflections and matching other kinds of knowledge, allowing building ways of being and acting considering one‟s own profession. Concerning narratives about CICLUS, I see the importance given to such experience, and the need to keep building such formation pathway. The need for formation focused on pedagogical questions was highlighted, and such support was perceived as part of the program, as a space dedicated to the teachers, in which they can relate problems experienced daily. It is indispensable to stimulate a formation movement, qualifying the processes of teaching and learning regarding university institutions, its achievement depending on institutional responsibility and on public policies. The research reaffirms that university pedagogy needs recognition as a field of knowledge inherent to the formative teacher. Thus, the formation of such professional might be redimensioned, and quality of higher education might be assumed as a social commitment.